Improved bounds on the size of separating hash families of short length - Penying Rochanakul (2020)
© 2020 by the Mathematical Association of Thailand. In this paper, we present some new upper bounds on the size of separating hash families of type {w1,w2} of short length, where the length N is not exceeding 2w2. A new proof for tight bounds on the size of separating hash families of type {1, w} is also given.